Damping Characteristics of a Novel Bellows Viscous Damper - Yang Chen; Chao Qin; Honghai Zhou; Zhenbang Xu; Anpeng Xu; Hang Li (Sensors, 2024)
Micro-vibrations during the operation of space remote sensing equipment can significantly affect optical imaging quality. To address this issue, a bellows-type viscous damper serves as an effective passive damping and vibration isolation solution. This paper introduces a bellows-type viscous damper with adjustable damping capabilities, designed for mid- to high-frequency applications. We developed a system damping model based on hydraulic fluid dynamics to examine how different factors—such as viscous coefficients, damping hole lengths, hole diameters, chamber pressures, and volumes—influence the damping characteristics. To validate the theoretical model, we constructed an experimental platform. The experimental results show that the theoretical damping curves closely match the measured data. Moreover, increasing the chamber pressure effectively enhances the damper’s damping coefficient, with the deviation from theoretical predictions being approximately 4%.